Is fairness intuitive?: an experiment accounting for subjective utility differences under time pressure - Merkel, Anna; Lohse, Johannes (Experimental economics, 2019)
Evidence from response time studies and time pressure experiments has led several authors to conclude that “fairness is intuitive”. In light of conflicting findings, we provide theoretical arguments showing under which conditions an increase in “fairness” due to time pressure indeed provides unambiguous evidence in favor of the “fairness is intuitive” hypothesis. Drawing on recent applications of the Drift Diffusion Model (Krajbich et al. in Nat Commun 6:7455, 2015a), we demonstrate how the subjective difficulty of making a choice affects decisions under time pressure and time delay, thereby making an unambiguous interpretation of time pressure effects contingent on the choice situation. To explore our theoretical considerations and to retest the “fairness is intuitive” hypothesis, we analyze choices in two-person binary dictator and prisoner’s dilemma games under time pressure or time delay. In addition, we manipulate the subjective difficulty of choosing the fair relative to the selfish option. Our main finding is that time pressure does not consistently promote fairness in situations where this would be predicted after accounting for choice difficulty. Hence, our results cast doubt on the hypothesis that “fairness is intuitive”.